Określenia chrześcijańskich duchownych Kościołów innych niż katolicki w polszczyźnie XVI wieku - Migdał, Jolanta (Poznańskie Spotkania Językoznawcze, 2015)
The article discusses 21 designations for Christian clergymen from Churches other than Catholic from the 16th century. They are general names of Orthodox and Protestant clergymen as well as the names of high-ranking priests and dignitaries of those Churches. The names mentioned have been excerpted from the published volumes of Słownik polszczyzny XVI wieku (“Dictionary of the 16thcentury Polish Language”). The article presents their origin and a consecutive history. What must be noted is quite big variety of the names of clergypersons of the denominations other than Catholic in the Polish language of the 16th century. Additionally, we can notice stability of those basic, most common designations. They are generally continued in contemporary Polish, not only in its specialist ecclesiastical variety.